Chemical Bond and Intermolecular Interactions - Li, Qingzhong; Scheiner, Steve; Yu, Zhiwu (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This reprint focuses on the geometrical and spectroscopic features as well as potential applications of halogen, chalcogen, pnictogen, tetrel, and triel bonds in chemical reactions, crystal engineering, molecular recognition, and biological systems. We particularly aim to present studies concerning the bonds formed between some novel important electron donors and acceptors, similarities and differences between these bonds, structures of the complexes composed of these bonds in solution and gas phases, spectroscopic methods for measuring these bonds in solution and gas phases, and applications of these bonds in chemical reactions, crystal engineering, molecular recognition, and biological systems.